(untitled) (Advances in Knowledge Representation, 2021)
Currently, ontologies are frequently used in sciences such as Linguistics, Information Science and Computer Science, especially in the areas of Conceptual Modeling and Knowledge Representation. One of the great challenges in ontologies is their costly and complex construction process, which can lead to errors in knowledge representation and information retrieval. The use of ontology methodologies and editors still represents a challenge to domain experts and information professionals, whose formation in the area does not privilege requirements for such activities. In this scenario, this paper presents a building methodology - OntoForInfoScience - and an ontology editor software - Onto4ALLEditor - whose main purpose is to provide a theoretical basis and functionalities of the tool in order to facilitate the development of ontologies by different types of users, mainly domain experts and information scientists. The research also includes an evaluation of ontology editors, currently available, and a brief discussion on the use and possibilities of OntoForInfoScience and Onto4ALLEditor in this context. As expected results of the proposed approach, it is intended to contribute to the popularization of the use of ontologies in Information Science and related areas.